Safety, tolerability, and pharmacokinetics (PK) of treprostinil palmitil inhalation powder (TPIP): a phase 1, randomised, double-blind, single- and multiple-dose study. (14th October 2021) - Ismat, F A; Usansky, H; Dhar Murthy, S; Zou, J; Teper, A
Abstract: Background/Introduction: Use of treprostinil in the treatment of pulmonary arterial hypertension (PAH) is limited by a short half-life and dose-limiting adverse events. TPIP, a dry powder formulation of the treprostinil prodrug treprostinil palmitil, is under investigation for PAH. In preclinical models, TPIP provided sustained treprostinil release in the lung and demonstrated sustained reduction of pulmonary arterial pressures. Purpose: To examine the safety, tolerability, and PK of single- and multiple-dose administration of once-daily (QD) TPIP in healthy volunteers. Methods: In this phase 1 study, healthy adults (aged 18–45 years) were randomised to receive single or multiple QD inhalation doses of TPIP. Single-dose participants received TPIP 112.5, 225, 450, or 675 μg (n=6 per dose) or placebo (n=2). Multiple-dose participants received TPIP 225 μg QD for 7 days (n=6), 112.5 μg QD for 4 days followed by 225 μg QD for 3 days (n=6), or placebo for 7 days (n=4). Results: Of 42 randomly assigned participants who received ≥1 dose, 41 (97.6%) completed the study. Of the single-dose TPIP–treated participants, 70.8% (n=17/24) experienced a treatment-emergent adverse event (TEAE) vs 0% (0/2) of placebo-treated participants; the most common TEAEs (≥15%) among TPIP-treated participants were cough (45.8%), dizziness (29.2%), throat irritation (20.8%), nausea (16.7%), and hypotension (16.7%). Of the multiple-dose TPIP–treated participants, 83.3% (n=10/12) experienced a TEAE vs 50.0% of placebo-treated participants (2/4); the most common TEAEs were cough (58.3% TPIP vs 50.0% placebo), headache (50.0% vs 0%), nausea (33.3% vs 0%), and dizziness (25.0% vs 0%). Overall, 69.0% of participants (29/42) experienced mild TEAEs and 16.7% (7/42) experienced moderate TEAEs; no severe or serious TEAEs occurred. TEAEs were more frequent with increasing TPIP doses. Participants titrated from TPIP 112.5 μg QD to 225 μg QD experienced fewer TEAEs than those who received 225 μg QD at treatment initiation; all TEAEs were mild. After single-dose TPIP treatment, treprostinil exposure was dose proportional, with mean (CV%) Cmax = 78.4–717 pg/mL (38.6-72.9%) and AUC(0–∞) = 1.09–5.48 h·ng/mL (11.5–30.0%). At steady-state (225 μg), the mean (CV%) of Cmax, Cmin, and AUC(0–t) were 193–228 pg/mL (32.9–46.4%), 17.6–22.8 ng/mL (43.7%-64.4%) and 1.68–1.82 ng·h/mL (28.7–36.6%), respectively. No steady-state accumulation was observed. Elimination t1/2 was 8.7–11.6 h after a single dose and 6.8–8.8 h at steady state. Plasma concentrations of treprostinil palmitil were below the limit of quantification (100 pg/mL) at all time points measured. Conclusions: In this phase 1 study, single and multiple TPIP dosing was generally well tolerated in healthy volunteers, with a PK profile that supports QD dosing. TEAEs were dose related; most were mild, none were severe or serious, and a titration schedule improved tolerability. These results support further examination of TPIP in patients with PAH. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): Insmed Incorporated